The Mother Nature Programme: a single-arm mixed-methods feasibility study of a group nature-based intervention for mothers experiencing postnatal mental health difficulties and their infants - Katherine Hall; Rosa Roberts; Katrina Turner; Lucinda Stanton; Sherien Elsheikh; Christopher Barnes; Beverly Shirkey; Lucy Duggan; Paul Moran; Jonathan Evans (Pilot and Feasibility Studies, 2026)
Abstract Background Postnatal mental health difficulties are common and often under-treated. Nature-based interventions have potential mental health benefits, but little research has focussed on their applicability postnatally. This study examined the acceptability and feasibility of delivering a co-designed, 5-week group nature-based intervention, The Mother Nature Programme (MNP), for mothers experiencing postnatal mental health difficulties and their infants, in preparation for a future trial. Methods A single-arm, mixed-methods feasibility study with a prospective pre/post design, delivered across six intervention groups. We recruited mothers self-reporting postnatal mental health difficulties, with infants under 12 months (extended to under 24 months in some groups), via community and third-sector organisations. The programme comprised weekly 2-h sessions of invitational activities guiding participants to notice and connect with the natural world. It was delivered in local urban outdoor settings, by a nature-based practitioner and peer support worker. Feasibility outcomes included recruitment, retention rates, attendance, and completeness of the following participant-reported outcome measures (collected at baseline and week 5): Edinburgh Postnatal Depression Scale (EPDS), Generalised Anxiety Disorder-7 Scale (GAD-7), Warwick-Edinburgh Mental Wellbeing Scale (WEMWBS), and Nature Relatedness Scale-6 (NR-6). We explored participants’ experiences of the intervention through a nested qualitative study. Analysis of feasibility outcomes was based on descriptive statistics. We analysed qualitative data thematically. Results Forty-three mothers, from diverse ethnic backgrounds, were enrolled in the study. Forty-two started the programme, of whom 90.5% (38/42) attended ≥ 3/5 sessions, and 47.6% (20/42) attended all five sessions. Post-intervention questionnaires were completed by 90.5% (38/42) for EPDS and GAD-7, and 81% (34/42) for all measures. Mean pre-post changes were EPDS − 3.6 (SD 4.3, n = 38), GAD-7 − 3.9 (SD 3.3, n = 38), WEMWBS + 8.6 (SD 8.0, n = 37), and NR-6 + 0.3 (SD 0.4, n = 34). We held interviews with 26 participants, and 6 women provided written feedback. Participants’ accounts of their experiences indicated high acceptability, and suggested modest ways in which to refine the intervention. Conclusions The MNP was feasible to deliver and highly acceptable amongst a diverse sample of postnatal mothers. Findings support the progression to a pilot randomised controlled trial, with integrated process and economic evaluations, before any assessment of effectiveness or cost-effectiveness is undertaken. Trial registration Not applicable; this was a non-randomised, single-arm feasibility study.